Application Of Talent Assessment Using Korn Ferry's 9 Box Matrix Concept at PT. Independent Talent Bank - Agus Tamrin Reni; Wahyu Satriyo Wicaksono; Della Jane Wijaya; Prianto Prianto; Febrian Hermawan (Jurnal Ilmu Sosial Mamangan, 2022)
Assessment and management of talent or what is often called Talent Management is one of the systems or efforts to get the right assessment of every employee in a company. This study was conducted to collect information on talent assessment using the Korn Ferry 9-box matrix concept at PT. independent talent bank. The study results from this assessment will serve to find and assess the ability of an employee to participate in the company to achieve company goals. In implementing this system, PT. BANK TALENT MANDIRI in performance and competency/potential assessment uses or refers to the concept of the 9-box Matrix (BOX MATRIX) by KORN FERRY which is used to analyze, display, and compare the performance and work potential of employees in 9 groups. In achieving performance and potential, the company uses key performance indicators (Key Performance Indicators (KPI)) based on individual work units. The project provides an overview of the employee talent mapping process in a company by following the process flow of talent management. We also discuss the practice of talent management in companies, and conclude by identifying several key patterns that are now, and will continue to influence talent management practice and studies in the future.